Investigating Scabies Pathogenesis and Therapeutic Potential of Nutmeg Extract in Experimental Animals - Erizal, Erizal; Hanafiah, Muhammad; Mudatsir, Mudatsir; Helmi, Teuku Zahrial (Heca Sentra Analitika, 2026)
Nutmeg (Myristica fragrans) is one of Indonesia’s agricultural commodities with recognized health benefits as a traditional medicine. In addition, nutmeg has potential as a natural treatment for scabies. This study aimed to evaluate the effectiveness of nutmeg fruit bioactive compounds in scabies treatment. Nutmeg extraction was conducted using three different solvents: ethanol, ethyl acetate, and n-hexane. The extract with the most dominant phytochemical composition was further analyzed for bioactive compounds using GC-MS and antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Subsequently, the extract was tested against Sarcoptes scabiei mites obtained from 15 stray cats. The effectiveness of nutmeg extract was evaluated in a spray formulation by observing mite mortality and lesion reduction. The results demonstrated that the ethanol extract of nutmeg fruit contained the most abundant phytochemicals, with 3-Methyl-2,5-Furandione (21.26%) and Maleic Anhydride (14.21%) as the dominant compounds. The ethanol extract also exhibited strong antioxidant activity with an IC₅₀ value of 21.41 ppm. In vitro testing showed 100% mite mortality at a 25% extract concentration within 24 hours, while in vivo testing on scabies-infected cats treated with the nutmeg spray extract revealed a significant reduction in scab lesions compared to the control group. These findings indicate that nutmeg extract possesses potent acaricidal and antioxidant properties, making it a promising alternative treatment for scabies. Further studies are required to refine the formulation and explore its clinical applications.